Spectroscopy of electric arc discharge plasma with admixtures of W, Mo, Cr - Lebid, A.V.; Veklich, A.N.; Tmenova, T.A. (Вопросы атомной науки и техники, 2016)
Plasma of electric arc discharges between composite Cu-W, Cu-Mo and Cu-Cr electrodes in argon flow and their spectra were studied by optical emission spectroscopy. Since values of oscillator strengths for W I, Mo I and Cr I presented in various databases are significantly different, selection of spectroscopic data for these elements (particularly oscillator strength) was expected to be useful for plasma diagnostics. The Boltzmann plot method was used as a tool for selection of appropriate spectral lines and their spectroscopic data. The main result of the paper are lists of W I, Mo I and Cr I spectral lines and spectroscopic data, which can be recommended for purposes of diagnostics of plasma with such metal impurities.